Prevalence, characteristics, and survival of children with esophageal atresia: A 32‐year population‐based study including 1, 417, 724 consecutive newborns. Issue 7 (2nd March 2016) - Cassina, Matteo; Ruol, Michele; Pertile, Riccardo; Midrio, Paola; Piffer, Silvano; Vicenzi, Virginia; Saugo, Mario; Stocco, Carmen Fiorella; Gamba, Piergiorgio; Clementi, Maurizio
Abstract : Background: Esophageal atresia (EA) is a congenital malformation of the upper gastrointestinal tract with an estimated prevalence varying from 1 in 2500 to 1 in 4500 births. The aim of this study was to describe the epidemiology of EA between 1981 and 2012 and evaluate patients' survival. Methods: This study used data from a population‐based Italian Congenital Malformation Registry. The survival status was ascertained by linking the registry records, vital records and the regional registries of patients. Kaplan‐Meier methods were used to estimate survival probabilities up to 25 years and Cox proportional hazards regression was used to evaluate factors that affected survival. Results: A total of 407 cases of EA were identified among 1, 417, 724 total births. After the exclusion of cases with chromosomal anomalies, 49.9% of the patients presented with at least one associated congenital anomaly. The 25‐year survival probability was 85.1% (95% confidence interval [CI], 80.8–89.4), with most deaths occurring during the first months of life. Patients' characteristics associated with decreased survival probability were low birth weight (hazard ratio, 3.7; 95% CI, 1.7–8.3) and presence of additional major defects (hazard ratio, 2.8; 95% CI, 1.3–6.0). A significant improvement in survival over the decades was observed for patients with nonisolated EA. Conclusion: This study detected a significant improvement in survival of individuals with EA over the past decades and identified the strongest predictors of mortality. These results will be important for the planning of the clinical management and formulation of prognosis when EA is diagnosed in a newborn. Birth Defects Research (Part A) 106:542–548, 2016. © 2016 Wiley Periodicals, Inc.